Microstructural evolution of sinter-forged Fe-Cr-Mo-C alloy depending on Cu addition - Oh, Min Chul; Kim, Moontae; Lee, Jisung; Ahn, Byungmin (Archives of Metallurgy and Materials, 2019)
Pre-alloyed Astaloy CrLTM (Fe-1.5 wt% Cr-0.2 wt% Mo), a commercial Fe-based alloy powder for high strength powder metallurgy products, was sintered and hot forged with additions of 0.5 wt% C and 0~2 wt% Cu. To investigate the influence of various Cu contents, the microstructural evolution was characterized using density measurements, scanning electron microscope (SEM) and electron backscatter diffraction (EBSD). Transverse rupture strength (TRS) was measured for each composition and processing stage. The correlation between Cu additions and properties of sinter-forged Fe-Cr-Mo-C alloy was discussed in detail.
Keywords: Cu addition; Electron back scatter diffraction; Fe-based alloys; High strength; Powder forging; Pre-alloyed powder; Processing stage; Transverse rupture strength; Astaloy CrLTM; Fe-based alloy; Microstructure; Powder forging; Pre-alloyed powder